Interfacial Curvature as a Potential Index for Prognosis of Colon Adenocarcinoma. Issue 3 (19th January 2021) - Gao, Jingwei; Yang, Chongqing; Li, Jianjun; Liu, Sidi; Ao, Zhuo; Han, Dong
Abstract: Tumor invasion and metastasis are complex interfacial mechanical processes between the tumor and its surrounding tissue, with the interfacial curvature of tumor playing an important role in cancer progression. In this study, the potential role of interfacial curvature in the prognosis of patients with colon adenocarcinoma is investigated. The front edge interfacial curvature of adenocarcinoma from biopsies of patients in different tumor, lymph node, and metastasis (TNM) stages are calculated and compared, and prognosis assessment is conducted using Kaplan–Meier and Cox proportional hazards regression analyses. Results reveal that patients with larger interfacial curvature of adenocarcinoma are more likely to belong to higher TNM stages. Concomitantly, in the same TNM stage, patients with increased adenocarcinoma interfacial curvature show worse prognosis with higher recurrence and lower survival rates. Besides, interfacial curvature is an independent prognostic factor for cause‐specific survival and relapse‐free survival among all selected patients. Mechanical models of colon adenocarcinoma invasion and metastasis are established to better understand the close association between interfacial curvature and tumor progression. The results together with hematoxylin and eosin staining indicate that metastasis in stages T3N0M0 and T3N1M0 may be linked to large interfacial curvatures. Therefore, interfacial curvature may serve as a potential index for predicting prognosis in patients with colon adenocarcinoma. Abstract : Interfacial curvature may serve as a potential index for predicting prognosis in patients with colon adenocarcinoma. Prognosis assessment results suggest that patients with a larger interfacial curvature show worse prognosis with higher recurrence and lower survival rates. The mechanical analysis reveals the important influence of interfacial curvature on colon adenocarcinoma invasion and metastasis.